PENGARUH KOMPETENSI, MOTIVASI DAN KOMITMEN TERHADAP KINERJA KARYAWAN PADA PTPN IV REGIONAL 1 KEBUN BANDAR SELAMAT - Sundari Alfriyansah; Anshari Putra (Mumtaz: Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the influence of organizational commitment, competence, and job satisfaction on employee productivity at PT. Perkebunan Nusantara IV Regional I Kebun Sei Silau, Asahan Regency using a quantitative and descriptive-explanatory approach. Data were obtained from 84 respondents through questionnaires, interviews, and documentation studies, then analyzed using multiple linear regression. The results of the study indicate that organizational commitment, competence, and job satisfaction simultaneously have a significant effect on employee productivity, and each variable partially contributes positively to improving performance. These findings emphasize the importance of strengthening committed, skilled, and satisfied human resources to improve organizational performance. The implications of this study for managerial practice are the need to develop commitment-enhancing programs, competency training, and job satisfaction-enhancing strategies to maximize productivity, while its contribution lies in providing relevant empirical evidence for Indonesian plantation companies in the context of improving HR performance.